PERENCANAAN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMIQ ORDER QUANTITY (EOQ) MENGGUNAKAN ALGORITMA GENETIKA (AG) (STUDI KASUS: PT. XYZ) - Heri Awalul Ilhamsah; Ade Novaliana Sari; Mu’alim Mu’alim (Politeknik Penerbangan Surabaya, 2020)
The PT. Refindo Intiselaras Indonesia is a manufacturing company that produces underground mining equipment. Rock Bolt is one of the main products produced. The problem that occurred in 2019 was that there was a delay in the production process because the material or raw material stock at PT.RII was lacking or not there, this could not happen to goods or service companies. This study uses the Economiq Order Quantity (EOQ) method approach with a genetic algorithm (AG) to solve the problems that occur. This study aims to minimize production delays, by purchasing optimal raw materials. Resulted in this research for the optimal purchase of raw materials in 2020, from January to August the required requirement for 2.5 mm is 18,186 Kg, 3.2 mm is 17,289 Kg, 3,4 mm is 19,740 Kg with a distance between orders for 3 months with a total purchase transaction of Rp. 26,783,237,193. The results of this study indicate that the total purchase of inventories generated by the Economiq Order Quantity (EOQ) method using a genetic algorithm (GA) is smaller than the company's total purchase cost of Rp. 28,662,000,000 thus saving costs of Rp. 1,878,762,807.